Cooperation between China and ASEAN states within the Belt and road initiative: education, culture, and tourism - Leping, Wang (Journal of the Belarusian State University. International Relations, 2024)
The Belt and road initiative, launched by China in 2013, has not only fostered the expansion of economic and political ties but also served as a catalyst for intensified cultural and humanitarian cooperation between the peoples of China and the ASEAN member states. The considerable potential for enhanced interaction is largely attributed to the inherent geographical proximity of these states. This article identifies and examines the distinctive characteristics of cultural and people-to-people interactions across three principal domains: education, culture, and tourism. Particular attention is paid to analysing successful initiatives and practices that contribute to deepening mutual understanding and respect between China and ASEAN members. These include cultural festivals, joint university alliances, cultural tourism weeks, and tourism initiatives. The author concludes that ASEAN states’ participation in the Belt and road intiative has enhanced the ties between China and these nations in the realms of education, culture, and tourism, thereby reinforcing regional interconnectedness and laying a solid foundation for friendship between their peoples.